Relação entre a severidade da periodontite e a deficiência da vitamina D - Priester, Alexandra Filippi (2024)
There is scientific evidence that vitamin D is associated with oral health and that its deficiency is related to periodontal disease, especially periodontitis. Periodontitis is characterized by inflammation of the periodontium and progressive destruction of tooth-supporting tissues. Vitamin D is a steroid hormone that regulates calcium and phosphorus levels in the body and plays an important role in immunomodulatory, antioxidant, and anti-inflammatory processes; in addition to bone formation and resorption, including in alveolar bone and teeth. This study analysed the relationship between the severity of periodontitis and vitamin D deficiency. This study was characterized as observational with a cross-sectional analytical design. The inclusion criteria for the sample included being male and having mild, moderate or severe periodontitis. Documentary, laboratory, and clinical examinations were performed on 40 male patients with periodontal disease. During the documentary examination, the periogram and an epidemiological form were completed. The collection of biological material (blood) was carried out to perform laboratory tests to determine serum levels of vitamin D. The clinical examination included a dental consultation with the purpose of diagnosing the presence of periodontal disease in the individuals' oral cavity, as well as filling out a dental oral health form. Thus, in this study, in relation to periodontitis, patients were classified into two groups: (1) mild to moderate, with attachment loss of 1 to 4 mm; and (2) severe, with attachment loss of at least 5 mm. Regarding vitamin D, values equal to or less than 50 nmol/L (or 20 ng/mL) were considered a deficiency. There was a statistically significant relationship (p ≤ 0.05) between the severity of periodontitis and levels of vitamin D deficiency; as well as teeth with furcation lesions were significantly related to vitamin D deficiency levels. However, there was no statistically significant relationship (p > 0.05) between the severity of periodontitis and some other variables analysed in this study, such as: sun frequency, sun exposure time, bleeding on probing, and bacterial plaque index. Vitamin D deficiency levels can influence the severity of periodontitis.